2016
DOI: 10.1051/0004-6361/201526565
|View full text |Cite
|
Sign up to set email alerts
|

Comet formation in collapsing pebble clouds

Abstract: Context. Comets are remnants of the icy planetesimals that formed beyond the ice line in the solar nebula. Growing from μm-sized dust and ice particles to km-sized objects is, however, difficult because of growth barriers and time scale constraints. The gravitational collapse of pebble clouds that formed through the streaming instability may provide a suitable mechanism for comet formation. Aims. We study the collisional compression of silica, ice, and silica/ice-mixed pebbles during gravitational collapse of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 56 publications
4
65
0
Order By: Relevance
“…As shown in Fig. 1, the pressure-porosity relations resulting from these parameters (for low, medium and high strength; Table 1) covers very well the range of experimental curves for dust agglomerates (Güttler et al 2009) and ice pebbles (Lorek et al 2016).…”
Section: Modeling Approachsupporting
confidence: 65%
See 2 more Smart Citations
“…As shown in Fig. 1, the pressure-porosity relations resulting from these parameters (for low, medium and high strength; Table 1) covers very well the range of experimental curves for dust agglomerates (Güttler et al 2009) and ice pebbles (Lorek et al 2016).…”
Section: Modeling Approachsupporting
confidence: 65%
“…Crush curve parameters P e and P s (Jutzi et al 2008), density of matrix material ρ s0 , initial bulk density ρ 0 , density of the compacted material ρ compact , initial distention α 0 , bulk modulus A, friction coefficient µ, cohesion Y 0 , average tensile strength Y T . Pressure-porosity relation (high strength) Pressure-porosity relation (medium strength) Pressure-porosity relation (low strength) Dust agglomerates (3D); Guetller et al, 2009 Ice pebbles (quasi 3D); Lorek et al, 2016 Fig. 1.…”
Section: Modeling Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…These planetesimals are expected to be composed of a high fraction of dust (silicates), which may explain why the rock-to-ice fractions inferred in minor planets and moons in the outer solar system (e.g., Schubert et al 2010) or the dust-to-ice ratio in comets (e.g., Rotundi et al 2015;Lorek et al 2016) are often significantly higher than the expected 1/2 to 1/3 value obtained from purely solar composition (e.g., Lodders 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The errors denote one standard deviation of the perihelion distances. The data were taken from the JPL Small-Body Database and the work by Kim et al (2014, their calculations have shown that the collision speeds during the collapse are low enough to not destroy the collapsing aggregates during collisons (Wahlberg Jansson & Johansen 2014;Lorek et al 2016).…”
Section: Introductionmentioning
confidence: 99%